(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article examines the current organizational framework of endometrial cancer prevention in Uzbekistan. The study analyzes screening coverage, stage distribution at diagnosis, risk factor profiles, and diagnostic resource availability across four regional oncological facilities over a five-year period. Evidence-based recommendations for systemic reform of preventive care infrastructure are proposed to reduce morbidity and mortality.